The Pattern of School Da'wa Movement: Restraining Radicalization Among Adolescent - Abdul Basit (Ijtimā`iyya: Journal of Muslim Society Research, 2016)
Previous researchers show that school is the most vulnerable institution induced by radical religious ideology. There are many factors that cause this, namely: the absence of strictly of religious regulation in school, psychological conditions of adolescent, the lack of religious comprehension, and uncontrolled religious organizations with various ideology in school. These conditions are required the pattern of the school da’wa movement that can be accepted by all adolescent. This research focused on constructing the pattern of da’wa movement which can be an alternative pattern of da’wa developed in schools.To get the data, this research conducted a qualitative research with phenomenological approach taking Purwokerto as the setting area. It applies observation as well as interview and focus group discussion with school leaders, teachers, students, activists of religious organizations, and religious leaders who understand the problems in this study. The main of data analysis is processed by qualitative research.To produce the patterns of school da’wa movement that can be accepted by all the communities, the school needs the pattern of integrative school da’wa movement within intra-curricular, co-curricular and extra-curricular activities. In practicing this da’wa movement pattern, the school should pay attention to the characteristics of the school, students' backgrounds, as well as involved stakeholders and the da’wa organizations.